Integration of fear learning and fear expression across the dorsoventral axis of the hippocampus - Marco N. Pompili; Noé Hamou; Sidney I. Wiener (Proceedings of the National Academy of Sciences, 2026)
Classically, the dorsal and ventral hippocampus are thought to play distinct roles in fear conditioning, with the dorsal hippocampus primarily handling information about environmental cues and contexts, and the ventral hippocampus more involved in emotional processing. Both functions are essential for the learning and expression of conditioned fear responses, but how these processes are integrated remains largely unexplored. In this study, we simultaneously recorded single-unit activity from the dorsal and ventral hippocampus during fear conditioning in male rats to identify the neural dynamics that may underlie these processes and their integration. As fear expression emerged, shifts in neural firing patterns were observed in both regions, with a stronger shift in ventral hippocampal activity, as expected. However, contrary to the prevailing view of the ventral hippocampus as central to anxiety and fear regulation, surprisingly, fear expression-related neuronal responses were more predominant in the dorsal hippocampus. In contrast, ventral hippocampal neuronal activity was more closely linked with the acquisition of conditioned fear. These features were combined in cell assemblies that emerged during fear conditioning, composed of both dorsal fear expression-responsive neurons and ventral fear learning-responsive cells. These multifactorial engrams, distributed along the hippocampal dorsoventral axis, provide a potential substrate for integrating fear acquisition and expression, thereby coordinating associative learning.